Attention for the speech of cleft lip and palate in speaker recognition - Lakshmi Prasanna P (Open Journal of Pain Medicine - Peertechz Publications, 2023)
Artificial Intelligence (AI) has become indispensable to all people, primarily for the purposes of speaker recognition, voice identification, educational purposes, workplace, and health care. Based on a speaker's voice characteristics, identification and recognition of the speaker is accomplished. The voice is affected by both intra- and interspeaker variability. In addition to this, a condition known as structural abnormalities can cause resonance, which can seriously affect voice quality. As a result, speakers may experience difficulties when using AI-based devices. The study aims to investigate the effects of speech with cleft lip and palate on speaker recognition. The review stated that even after surgery, some people with cleft lip and palate exhibit hypernasality and poor speech intelligibility depending on the severity of the cleft. The author discovered that artificial intelligence has been applied to surgical procedures. In children with corrected cleft lip and palate, acoustic analysis revealed poor benchmarking for speaker identification. The most prevalent type of hypernasality also affects speech intelligibility. Thus, more research on speaker recognition using different algorithms and hypernasality is essential. These can help speakers who have CLP to use AI freely and without any issues. Even with its flaws, people with CLP can still learn more about using AI.